Profile of Students’ Mathematical Representation in Solving Trigonometric Problems Based on Mathematics Ability - Hasanah, Sri Indriati; Basri, Hasan; Zayyadi, Moh. (FKIP Universitas Lampung, 2022)
Profile of students' mathematical representation in solving trigonometric problems based on mathematics ability. Objectives: This study aims to determine and describe students' mathematical representational abilities in solving trigonometric problems based on mathematical abilities. Methods: This research is a qualitative research with a descriptive approach, in this study 3 subjects were selected from 36 students. Data was collected through tests and interviews. Findings: Students with high math skills are good at using visual representations and quite good at using equation representations or mathematical expressions. Students with moderate mathematical ability are quite good at using visual representations and representations of mathematical equations or expressions. Students with low mathematical ability are quite good at using visual representations but are still not good at using representations of mathematical equations or expressions. Conclusion: The three research subjects only involved visual representations and mathematical equations or expressions, but did not involve representations of words or written text in solving problems. Keywords: mathematical representation, problem solving, and mathematical ability.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202227